Upaya Pencegahan Hasil Positif Palsu melalui Edukasi Pemeriksaan Narkotika pada Siswa Sekolah Mengenah Kejuruan - Mamay Mamay; Lia Mar’atiningsih; Muhammad Hadi Sulhan; Astari Nurisani; Gina Nafsa Mutmaina; Meti Rizki Utari (Fakultas Teknik Universitas Cenderawasih, 2024)
Vocational High School (SMK) is a place of education that prepares its students to be ready to face the world of work. Drug tests are often carried out targeting prospective employees as a requirement to enter the workplace in an agency. Knowing about drug tests is very important for Vocational High School (SMK) students who will enter the world of work. Education about false positive results in drug tests is very important for SMK students who will enter the world of work. The right education program can increase efforts to prevent false positives in drug tests when entering the world of work for SMK graduates. To increase knowledge related to drug tests and false positive detection, health education is carried out and also a demonstration of drug tests on urine. Before and after education, each student takes a pre-test and post-test through a questionnaire to see the increase in their knowledge. After community service was carried out, with education about drug tests, there was an increase in understanding about drug tests, the drug test process with immunochromatography (ICT) and the detection of false positive results in drug tests.